MODERATING ROLE OF BOARD INDEPENDENCE IN THE EFFECT OF TAXES, DEBT COVENANT, AND OWNERSHIP STRUCTURE ON TRANSER PRICING - Adiba, Rara; Solikhah, Badingatus ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2025)
Transfer pricing practices continue to be a challenge in many countries because they often conflict with applicable tax laws and are frequently used to reduce the tax burden that should be paid. This study aims to examine how taxes, debt covenants, and ownership structure influence transfer pricing practices, as well as how board independence acts as a moderating variable. The analysis was conducted using a quantitative method, with secondary data obtained from company financial reports accessed through the Indonesia Stock Exchange (IDX) website and the Refinitiv database. The sample includes 844 non-financial companies listed on the IDX between 2020 and 2024, resulting in 4,220 observation units. Additionally, this research considers company size as a control variable. The results show that taxes and debt covenants positively influence transfer pricing, while ownership structure has a negative impact. The role of board independence does not significantly moderate the relationship between these variables and transfer pricing. Based on these findings, companies are advised to increase foreign and institutional ownership to reduce transfer pricing practices that could pose long-term risks. The novelty of this study lies in its broader data coverage, including all non-financial companies in Indonesia, to evaluate the influence of board independence more generally within the context of national corporate governance.